INFLUENCE OF HYDROTHERMAL CONDITIONS AND TECHNOLOGICAL FACTORS OF GROWING ON DEVELOPMENT AND GROWTH OF WINTER CULTURES IN THE AUTUMN PERIOD - Полторецкий, Сергей; Свистунова, Ирина; Яремчук, Любовь; Худолей, Людмила; Барановский, Олег (SWorldJournal, 2021)
The article presents the results of research of the impact of technological measures of cultivation and hydrothermal resources on the growth and development of winter cereals in the autumn in the Forest-Steppe right bank. There was an increase in the numb